A Novel Current Calculation Method Based on Temperature Rise of Current-Carrying Conductor. (24th September 2020) - Lv, Sen; Zong, Ming
Abstract : Smart grid is the inevitable trend of power grid technology development. As an important terminal apparatus in the power grid, the overload protection method of bimetal used by traditional miniature circuit breakers (MCBs) is difficult to meet the requirements of smart grid. Bimetal uses the thermal effect of current for overload protection, so in this paper, the thermal effect is used to calculate the current. Also, all current carrying conductors except superconductors will generate heat, and the heat will not be saturated, which can meet the characteristics of miniature circuit breakers with small volume and large current. Compared with other current calculation methods, the proposed method has simple structure and wide measurement range, which is an effective way to solve the problem of intelligent MCBs. After derivation, the algorithm in this paper is not affected by the convection coefficient. The experimental results show that the error of the algorithm is less than 5%.